Digital database on shrimp farming in coastal watershed of Cuddalore District, Tamil Nadu - Nila Rekha, P.; Gangadharan, R.; Dharshini, Shirley; Clark, Wilmart; Ramanathan, G.; Vimala, Deboral; Panigrahi, A.; Gopal, C. (Indian Journal of Fisheries, 2018)
Brackishwater shrimp farming is essentially a coastal farming activity, making use of the marginal land and water resources resulting in economic benefits, providing livelihood option for the coastal poor and contributing to the national GDP. Getting successful crop by the farmers is indeed a great accomplishment since the disease threat always hovers around shrimp culture. This warrants the adoption of better management practices starting from the pond construction till the harvest of the shrimp with a collective action among the shrimp farmers in a cluster of farms with respect to stocking, adoption of biosecurity measures, disease management and discharge of treated water. For practically enforcing this though farmers’ associations, development of spatial database is a prerequisite and it is a relatively easy task in this age of information revolution. With this background, a digital information system has been built using ArcGIS 10.0 for the shrimp farms in the coastal watershed of Cuddalore District in Tamil Nadu primarily to aid farmers. The developed spatial database contains information about all the shrimp farms in Cuddalore District and it has been digitised from GeoEye with the cadastral map in the scale of 1:5000. Total 4.0 km2 of shrimp farm area with 351 individual ponds spread over six clusters of farms has been digitised with their survey number. Field surveys were conducted to verify the satellite data. Details of the farms’were collected using a structured questionnaire and have been incorporated in the database. Using this database both spatial and statistical information can be analysed and managed for querying, decision making and resource management. This digital information will also be handy for the policymakers for licensing the farm, monitoring growth and to enforce the environmental guidelines.